Pencegahan Anemia Defisiensi Besi pada Remaja melalui Penyuluhan Gizi Seimbang - Sawitri Dewi; Alfi Noviyana (LPPM Akbid Harapan Ibu Pekalongan, 2022)
Adolescence is the second critical period for physical growth after the first year of life. Indonesia is home to about45 million adolescent boys and girls or equivalent to 18% of the total population. Indonesia suffers from a fairly high nutritional deficiency accompanied by an increasing prevalence of obesity – which is known as the Double Burden of Nutrition Problems. During adolescence, there are specific biological and physiological changes in the body according to gender so that nutritional needs become different. Adolescents are increasingly considered important as potential agents of nutritional change in Indonesia because they play a role in cutting the intergenerational chain of poverty and malnutrition. The Tanjung Muhammadiyah Women's Orphanage is one of the private institutions that manages and protects young orphaned and orphaned girls. In the orphanage there are about 34 young women who attend school from elementary school to high school. Every day the children in this orphanage get food rations from the orphanage's kitchen with a standard menu. Temporary data obtained that most of the teenagers in this orphanage suffer from mild anemia, one of the possible causes is a lack of knowledge about balanced nutrition. The purpose of providing counseling to adolescents in this orphanage is to provide knowledge and understanding of nutritional needs and fulfillment, especially for young women as an effort to prevent iron deficiency anemia in adolescents